Peningkatan Profesionalisme Guru SD melalui Publikasi Ilmiah di Jurnal Nasional berbasis OJS : Pengabdian - Hevy Risqi Maharani; Mochamad Abdul Basir; Mohamad Aminudin; Dyana Wijayanti; Imam Kusmaryono; Nila Ubaidah; Muhamad Afandi; Mayana Agustyani (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Scientific publication is one of the activities that teachers must carry out in continuous professional development activities as a condition for promotion to functional positions. Therefore, it is important for teachers to be able to publish their scientific work in OJS-based national journals. The aim of the training by the Mathematics Education Study Program service team at Universitas Islam Sultan Agung is to increase the professionalism of teachers at SD N 02 Tambakrejo Gayamsari through the publication of scientific works in OJS-based national journals. The output of service activities is that the teachers of SD N 02 Tambakrejo Gayamsari have the ability to publish scientific works in OJS-based national journals so that later they can increase the teacher's credit score for promotion to functional positions. Activities were carried out offline at SD N 02 Tambakrejo Gayamsari. The training implementation method includes lectures, demonstrations, questions and answers, practice and assistance to teachers at SD N 02 Tambakrejo Gayamsari in the process of publishing scientific articles in OJS-based national journals. Training participants actively participated in activities from start to finish and participants gave positive responses to the implementation of service activities.